Cattle fattening in Leucaena leucocephala grazing: some economic and financial indicators for making decisions - Cino, Delia M.; D?az, Asl?n; Castillo, Emilio; Hern?ndez, Jorge Luis (Cuban Journal of Agricultural Science, 2011)
From an economic perspective, a set of indicators was studied for cattle fattening technologies in Leucaena leucocephala (variety Peru) grazing, with supplementation and without it. The research was developed at the Institute of Animal Science, in systems with lots of 150 animals of the genotypes ? Holstein x ? commercial Zebu and Cuban Charolais: five with natural pasture and CT-115 (Pennisetum purpureum cv.), and two with star grass (Cynodon nlemfuencis). Cost records per treatment were elaborated and the cost/animal, the cost/kg LW, the cost/ha, the cost/$, the benefit/cost (B/C), and the point of equilibrium (kg meat and animals) were calculated. As financial indicators, the gross margin, the gross income and the direct costs per hectare and the profitability and the recovery of the investment (years) were estimated. The American dollar (USD) was used as pattern, to make the analysis of technology transference and the safe of importations. The utilization of the silvopastoral system with leucaena was positive, regardless the handling of inputs and applied systems. Nevertheless, the best indicators corresponded to the non-supplemented systems with lower costs/kg, per ha, animal and LW produced and higher B/C, although the Charolais showed similar indicators, due to the favorable economic response to the application of supplements. The most intensive systems presented the highest gross margins and gross incomes per hectare and higher level of direct costs. The profitability and recovery of investments were favorable to the use of lower inputs. The analysis shows the utility of the use of these indicators to make viable the selection of productive alternatives, the optimization of resources and the potential safe of importations to Cuba. Key words: cattle fattening, leucaena, economic and financial indicators.